Effect of Gamma radiation on the experimental infection with giardia in albino Norvegicus rats - folk al-Dabbagh; Zuhair Fethouhi Rahimou (College of Education for Pure Sciences, 2010)
ABSTRACT The present study included isolation of Giardia lamblia from stools of patients then inoculation of giardiasis in the rat, Rattus rattus norvegicus. The induction was of two forms: parasites radiated and unradiated aiming to throaw a light on the effect of gamma radiation on virulence of infection, duration of resistance, and a period of existence in the host. The criteria which were used in this study are the mean of the production of cysts, reduction of host weight, and effect of infection on histological changes of the intestine via villi /crypts ratio. The cysts of G. lamblia were irradiated with Gamma rays in a dose 0.1122 × 10-3 ml rad/ hr and 1.5624 ×10-3 ml rad/hr for 2 and 24 hours respectively. A comparison was made between results of radiated and a unradiated G. lamblia ccysts after oral administration of dose 2 ×104 cyst/ml. The results revealed that radiation reduced the duration of resistance and existence of the parasites in the host body - The radiation reduced the resistance duration and existence of the parasite in host body, and reduce the production of cysts in highly significant level. - Radiation did not reduce reduction the weight of the host infested with radiated parasites. - Reduction in villi/crypts ratio is less animals infected with radiated parasites than those of unradiated ones.